PENGARUH GAYA BELAJAR TERHADAP PRESTASI BELAJAR SISWA KELAS XI IPS PADA MATA PELAJARAN EKONOMI DI SMAN 1 BANGKINANG KOTA - Hardianti, Tin; Kartikowati, Sri; Haryana, Gani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to know: 1) description of the learning styles of students. 2) effect of student learning styles on student achievement. The population in this study were students of class XI IPS in Economics subjects at SMAN 1 Bangkinang Kota, amount to 128 students, and the sample in this study was 97 students. Data collecting techniques used questionnaires and documentation. Data analysis method used is chi square test analysis. The results of this study showed that dominant learning styles in class XI IPS are visual learning styles as much 39 people (40.2%), and the tendency of student learning styles included in the medium category 40 people (41.23). The results of the chi square test analysis show that chi square counts 18.215 <21.03 chi square table and Asymp sig. (2- tailed) value. 0.109> 0.05. This means that the Ho hypothesis is accepted. So it can be concluded that there is no significant influence between learning styles and learning achievement of students of class XI IPS in SMAN 1 Bangkinang Kota.Key Words: Learning style, Learning achievement